iF product design award yearbook 2010 (Birkhauser, 2010)
The book presents all the winners in the categories of consumer electronics and telecommunications, computers, office and business, lighting, house and home, leisure and lifestyle, industry and building, medicine, public and interior design, and transportation, as well as those in the advanced studies category